A comparative analysis of the cycle fecundity rates associated with ovarian hyperstimulation along with IUI versus medical management in the treatment of mild to moderate oligozoospermia in males - Acharyya, Tanaya; Choudhury, Arun Paul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: To compare the pregnancy rate in infertile couples with mild to moderate oligozoospermia receiving ovarian hyperstimulation and IUI, with that of medical management with CC. Methods: A total 120 couples with males having sperm concentration between 5 to 20 million/ml, normal serum gonadotropins and testosterone, and a presumptively fertile partner were enrolled in this prospective clinical study, during the study period of 19 months, 31st January 2019 till 1st September 2020. 120 couples were divided randomly into two groups A (n=60) and B (n=60). In group A, 60 couples were subdivided equally into 3 groups, each having 20 couples. Ovarian hyperstimulation protocols with IUI were used in different subgroups in group A. A total of 216 IUI cycles done for 60 couples. While in group B, 60 males with oligozoospermia were prescribed CC treatment 25mg/day on alternate days for 3 months. Results: Out of 60 patients in group A, 24 achieved pregnancy with a cycle fecundity rate of 4% in CC+IUI, 9.87% in HMG+CC+IUI and 21.67% in HMG+IUI. 5 out of 60 patients in group B achieved pregnancy with cycle fecundity rate of 2.78%. Conclusions: These data suggest that acceptable pregnancy rates can be achieved with IUI combined with ovarian hyperstimulation in males with oligozoospermia. The role of CC treatment in males with oligozoospermia in improving the pregnancy outcome is extremely mearge. Thus, owing to the cost effectiveness and non-invasive modality, IUI is preferred prior to other more invasive and potentially costly reproductive technologies in the treatment of male factor subfertility.